Bite the bullet [videorecording (DVD)] - Brooks, Richard, 1912-1992; Hackman, Gene; Bergen, Candice, 1946-; Coburn, James; Johnson, Ben, 1918-1996 (Columbia TriStar Home Entertainment, 2004)
A former Rough Rider, a lovely but shady lady-in-distress, a drifting ex-cowboy, a young reckless cowboy, a haughty English sportsman, and a gutsy Pony Express rider come together to battle the trials of the rugged West in a grueling 700-mile horse race.